2018
DOI: 10.1103/physrevlett.120.136404
|View full text |Cite
|
Sign up to set email alerts
|

Local Real-Space View of the Achiral 1TTiSe2 2×2×2

Abstract: The transition metal dichalcogenide 1T-TiSe_{2}-two-dimensional layered material undergoing a commensurate 2×2×2 charge density wave (CDW) transition with a weak periodic lattice distortion (PLD) below ≈200  K. Scanning tunneling microscopy (STM) combined with intentionally introduced interstitial Ti atoms allows us to go beyond the usual spatial resolution of STM and to intimately probe the three-dimensional character of the PLD. Furthermore, the inversion-symmetric achiral nature of the CDW in the z directio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
27
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 27 publications
0
27
0
Order By: Relevance
“…By contrast, a particularly unconventional scenario is the gyrotropic order [4][5][6][7][8], where chirality spontaneously emerges across a phase transition as the electron system breaks the relevant symmetries of an originally achiral lattice. Such a gyrotropic order, proposed as the quantum analogue of the cholesteric liquid crystals, has attracted significant interest [4][5][6][7][8][9][10][11][12][13][14][15][16][17]. However, to date, a clear observation and manipulation of the gyrotropic order remain challenging.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…By contrast, a particularly unconventional scenario is the gyrotropic order [4][5][6][7][8], where chirality spontaneously emerges across a phase transition as the electron system breaks the relevant symmetries of an originally achiral lattice. Such a gyrotropic order, proposed as the quantum analogue of the cholesteric liquid crystals, has attracted significant interest [4][5][6][7][8][9][10][11][12][13][14][15][16][17]. However, to date, a clear observation and manipulation of the gyrotropic order remain challenging.…”
mentioning
confidence: 99%
“…In classical liquids, this is known as the cholesteric liquid crystal. In quantum materials, despite fundamental interest [4][5][6][7][8][9][10][11][12][13][14][15][16], a clear observation of the gyrotropic order remains lacking.For a condensed matter system, one route to obtain chirality is to look for low-symmetry materials that naturally crystalize in lattice-structures that are free of any mirror, inversion and roto-inversion symmetries, i.e., chiral crystals [3]. Representative chiral crystal materials include quartz, tellurium, carbon nanotubes and twisted bilayer graphene.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Striped contrast in the HT phase was proposed to represent chains of Ta dimers instead of trimers [20], however, the stripes are also consistent with the surface Te atoms undergoing the bulk distortion [21,22]. Mapping the bulk structure and disentangling lattice displacements from charge modulations are thus required for resolving the nature of density waves in 1T 0 -TaTe 2 and layered TMDs in general [23][24][25].…”
mentioning
confidence: 99%
“…Thus, it is important to experimentally investigate the presence or absence of correlation effects as well as the role of hybridization in the electronic structure of 1T -TiSe 2 . Further, it has been reported that 1T -TiSe 2 exhibits a chiral CDW order [26], but this is still under debate [27]. Very recently, a study showed gyrotropic order in 1T -TiSe 2 , in the form of chiral order induced by midinfrared circularly polarized light in an originally achiral lattice [28].…”
Section: Introductionmentioning
confidence: 99%